Pressure-regulated volume control vs. volume control ventilation in healthy and injured rabbit lung: An experimental study. Issue 10 (October 2016) - Porra, Liisa; Bayat, Sam; Malaspinas, Iliona; Albu, Gergely; Doras, Camille; Broche, Ludovic; Strengell, Satu; Peták, Ferenc; Habre, Walid
Abstract : BACKGROUND: It is not well understood how different ventilation modes affect the regional distribution of ventilation, particularly within the injured lung. OBJECTIVES: We compared respiratory mechanics, lung aeration and regional specific ventilation ( ) distributions in healthy and surfactant-depleted rabbits ventilated with pressure-regulated volume control (PRVC) mode with a decelerating inspiratory flow or with volume control (VC) mode. DESIGN: Randomised experimental study. ANIMALS AND INTERVENTIONS: New Zealand white rabbits ( n  = 8) were anaesthetised, paralysed and mechanically ventilated either with VC or PRVC mode (tidal volume: 7 ml kg −1 ; rate: 40 min −1 ; positive end-expiratory pressure (PEEP): 3 cmH2 O), at baseline and after lung injury induced by lung lavage. MAIN OUTCOME MEASURES: Airway resistance (Raw), respiratory tissue damping (G) and elastance (H) were measured by low-frequency forced oscillations. Synchrotron radiation computed tomography during stable xenon wash-in was used to measure regional lung aeration and specific ventilation and the relative fraction of nonaerated, trapped, normally, poorly and hyperinflated lung regions. RESULTS: Lung lavage significantly elevated peak inspiratory pressure (PIP) ( P  < 0.001). PIP was lower on PRVC compared with VC mode (−12.7 ± 1.7%, P  < 0.001). No significant differences in respiratory mechanics, regional ventilation distribution, strain or blood oxygenation could be detected between the two ventilation modes. CONCLUSION: A decelerating flow pattern (PRVC) resulted in equivalent regional ventilation distribution, respiratory mechanics and gas exchange, in both normal and mechanically heterogeneous lungs with, however, a significantly lower peak pressure. Our data suggest that the lower PIP on PRVC ventilation was because of the decelerating flow pattern rather than the ventilation distribution.